STRATEGI PENGELOLAAN KAWASAN KONSERVASI TAMAN WISATA ALAM PULAU BURUNG DAN PULAU SUWANGI DI KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Suriansyah, Suriansyah; Kadir, Syarifuddin; Istikowati, Wiwin Tyas (Lambung Mangkurat University-Indonesia, 2025)
The Bird Island and Suwangi Island Nature Tourism Parks (TWA Busuwa) have great potential to be developed as ecotourism because they are supported by the natural resources of the two islands, the beauty of the natural scenery is very supportive of being used as a tourist attraction, besides that there are also local cultural customs that are still preserved. Carried out by the people who live on the two islands. The research was conducted at TWA Bird Island and Suwangi Island, which administratively are located in Pulau Panjang Village, Simpang Empat District and Batulicin Village, Batulicin District, Tanah Bumbu Regency, South Kalimantan Province. The research was carried out for 3 months starting from the preparation stages, data collection and data analysis. The method used in this research is purposive sampling, calculated from the results of questionnaires, recommended from the results of interviews in the field, spatial analysis and SWOT analysis. The results of the research were that Bird Island had a dipterocarp forest ecosystem covering an area of ±28,169 ha, a mangrove forest ecosystem covering an area of ±452,962 ha and an artificial ecosystem covering an area of 64,075 ha. Suwangi Island has a dipterocarp ecosystem type covering an area of ±356,185 ha, a mangrove forest ecosystem covering an area of ±235,111 ha and an artificial ecosystem covering an area of ±103,148 ha. Analysis of animal distribution maps in TWA Bird Island and Suwangi Island, there are 6 types of protected animals found in these places, including the proboscis monkey (Nasalis larvatus), white-bellied kangkareng (Anthracoceros albirostris), black kangkareng (Anthracoceros malayanus), rhinoceros hornbill (Buceros rhinoceros), golden hornbill (Rhyticeros undulatus) and estuarine crocodile (Crocodylus porosus).